Examining protocol compliance and self-report congruence between daily diaries and event-contingent ecological momentary assessments of college student drinking. (November 2020) - Hultgren, Brittney A.; Scaglione, Nichole M.; Buben, Alex; Turrisi, Rob
Highlights: A Alcohol use and intoxication were similar in event-contingent EMA and daily diaries. Daily diaries had higher compliance than event-contingent EMA on drinking days. Missing EMA associated with higher alcohol use and intoxication reported in daily diaries. Abstract: Background: Daily diaries and ecological momentary assessments (EMA) are frequently used to assess event-level college student drinking. While both methods have advantages, they also raise questions about data validity, particularly in regard to alcohol's impact on protocol compliance. The current study examined congruence in drinking behaviors reported via retrospective daily diaries and event-contingent drinking logs, protocol compliance with each method, and the extent to which alcohol consumption impacted compliance. Methods: Participants were first-semester college women (n = 69) who reported 4+ drinks during an occasion at least once in the past month. Participants reported the number of drinks consumed and subjective intoxication using a 14-day EMA protocol. Event-contingent drinking logs (via self-initiated EMA) assessed behavior immediately after each drinking event; daily diaries assessed behaviors from the previous day. Pairwise correlations examined congruence between drinking logs and corresponding daily dairies; protocol compliance was examined through descriptive analysis of data missingness; and multilevel regression models assessed the associations between protocol compliance, alcohol consumption, and subjective intoxication. Results: Drinking log and daily diary reports were highly correlated ( r 's = 0.70 to 0.93). On drinking days, diary reports had higher protocol compliance (96.0%) compared to momentary drinking logs (41.4%). Drinking log missingness was associated with greater alcohol use and subjective intoxication reported in the corresponding daily diary (p' s < 0.05) . Conclusions: Similarities in reports of alcohol consumption and subjective intoxication, coupled with higher missingness of momentary assessments suggest daily diaries may have methodological advantages and unique utility in supplementing momentary assessments.